OPPORTUNITIES AND CHALLENGES FOR VIETNAM LOGISTICS SERVICE SECTOR IN THE CONTEXT OF INTEGRATION - Linh, Ngo Cao Hoai (International Journal of Psychosocial Rehabilitation, 2020)
The article discusses the basic difficulties and challenges which Vietnamese logistics service providers faced and facing to propose synchronized solutions to reduce logistics costs contributing actively to increase the competitiveness of Vietnam’s goods in the context of deep integration with the world.